CHALLENGES FACING MALAYSIA IN EXPANDING ITS ISLAMIC FINTECH LANDSCAPE & POSSIBLE REMEDIES - Kinan Salim; Abubakar Ilyas (Jurnal Internasional Ekonomi Islam, 2020)
Despite being a dynamic hub for the Islamic financial products and services, Malaysia’s Islamic fintech landscape does not meet expectations. With a number of challenges such as stringent regulations, lack of adequate funding, shortage of a skilled workforce, fierce conventional competitors etc. the future growth and progress might only remain an unfulfilled dream if they are not addressed timely. This paper is aimed at critically discussing these challenges faced by such companies. Also it aims at proposing potential measures to overcome the highlighted issues. But in order to validate the mentioned challenges and the potential remedies, an interview based approach is employed. The top and middle management of five full-fledged Islamic fintech companies were interviewed with the aim of ensuring whether the mentioned challenges actually exist or not. And whether the proposed solutions are practicable. Based on the findings from the interviews, it is observed that almost all the mentioned challenges are recognized by the companies. Although not all were in consensus regarding every issue, but in general they saw the challenges as legitimate. The proposed solutions were also well received and recognized as beneficial for the companies. Another finding from the interviews was additional challenges the companies saw as worrisome, such as lack of awareness and technological ignorance among the masses. The paper concludes with the recommendation for the relevant authorities to address the highlighted issues with seriousness. Further research may be carried out to provide solutions for the additional issues pointed out by the companies